APPLICATION OF A PNEUMONIA PREVENTION BUNDLE IN A PEDIATRIC ICU. - Vargas Cardoso, Monique Eva; de Souza, Andressa (Journal of Nursing UFPE / Revista de Enfermagem UFPE, 2021)
Objective: to evaluate the impact of a prevention bundle for Mechanical Ventilation Associated Pneumonia in a Pediatric Intensive Care Unit. Method: This is a quantitative and quasiexperimental study conducted in a pediatric Intensive Care Unit. All Patients in Mechanical Ventilation were analyzed during a period of two years (in the pre- and post-intervention phases), in relation to the occurrence of Mechanical Ventilation Associated Pneumonia. The following items were verified from the adopted bundle: high head; prevention of gastric ulcer; oral hygiene and daily assessment of sedation. Results: it is shown that there was a decrease in the incidence of pneumonia (P=0.002) and in the mean time of use of the ventilator after the application of the protocol (P=0.045). A significant difference was detected regarding bacteria, with predominance of Gram-negative in the group of patients without the use of the protocol, compared to the group with the bundle (P=0.001). Conclusion: It was concluded that the risk factors for VAP are considered modifiable and can be prevented through the creation of specific care protocols. It is argued that the implementation of bundle in pediatrics can reduce nosocomial infections, highlighting the pneumonia reported in this study.